Impact of ocean stratification characteristics on identifiability of internal wave trails in synthetic aperture radar images - Zhechao YANG; Liqun REN; Changhong ZHI; Yunxiang YOU; Hongwei WANG (Zhongguo Jianchuan Yanjiu)
ObjectivesAiming at the problem of the identifiability of underwater vehicle wave trails in synthetic aperture radar (SAR) images in a density stratified environment, this study establishes a theoretical solution model and quantitative analysis method. MethodBased on the statistical information of ocean stratification characteristics, a theory of internal waves induced by equivalent sources of moving mass and momentum is designed. The modulated wave spectrum of each statistically independent sea surface unit and the corresponding intensity distribution mapped in the SAR images are calculated, and then the texture feature information of the internal wave trails in the images is extracted based on the gray level co-occurrence matrix. ResultsThe results show that under specific parameter conditions, the identifiable interval of internal wave trails in SAR images occurs when the maximum buoyancy frequency is greater than 0.02 rad/s and the corresponding depth is less than 100 m. ConclusionThe proposed method can be used to effectively calculate and analyze the identifiability of internal wave trails in any density stratified environment, providing a basis for underwater target detection.